Dar al-Islam -- Dar al-ḥarb : territories, people, identities - Calasso, Giovanna.; Lancioni, Giuliano. (Studies in Islamic Law and Society, 2017)
This is the first collection of studies entirely devoted to the terminological pair dār al-islām / dar al-ḥarb , "the abode of Islam" and "the abode of war", apparently widely known as representative of "the Islamic vision" of the world, but in fact almost unexplored. A team of specialists in different fields of Islamic studies investigates the issue in its historical and conceptual origins as well as in its reception within the different genres of Muslim written production. In contrast to the fixed and permanent categories they are currently identified with, the multifaceted character of these two notions and their shifting meanings is set out through the analysis of a wide range of contexts and sources, from the middle ages up to modern times. Contributors are Francisco Apellániz, Michel Balivet, Giovanna Calasso, Alessandro Cancian, Éric Chaumont, Roberta Denaro, Maribel Fierro, Chiara Formichi, Yohanan Friedmann, Giuliano Lancioni, Yaacov Lev, Nicola Melis, Luis Molina, Antonino Pellitteri, Camille Rhoné-Quer, Francesca Romana Romani, Biancamaria Scarcia Amoretti, Roberto Tottoli, Raoul Villano, Eleonora Di Vincenzo and Francesco Zappa.